2021
DOI: 10.1007/s12144-021-02059-x
|View full text |Cite
|
Sign up to set email alerts
|

Why people were less compliant with public health regulations during the second wave of the Covid-19 outbreak: The role of trust in governmental organizations, future anxiety, fatigue, and Covid-19 risk perception

Abstract: Trust in governmental organizations is a crucial factor in terms of encouraging people to conform to public health regulations, such as those recommended to slow down the spread of SARS-CoV-2. However, trust in governmental organizations tends to decline over time, reducing the compliance with public health regulations. This study aimed at exploring, first, the role of future anxiety and fatigue as serial mediators of the relationship between trust in governmental organizations and protective behaviors, and, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 72 publications
(106 reference statements)
4
38
0
1
Order By: Relevance
“…This negative perception might be due to the uncertainty surrounding the COVID-19 virus; governmental efforts were often misaligned with media coverage and a mix of misinformation, leading to a lack of trust in governmental efforts (78,82,83). These findings display that perceived governmental efforts directly impact willingness to vaccinate (84,85). This finding reflects upon the pandemic's political ramifications (84,86,87) that have been introduced and its negative impact on citizens' willingness to vaccinate.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This negative perception might be due to the uncertainty surrounding the COVID-19 virus; governmental efforts were often misaligned with media coverage and a mix of misinformation, leading to a lack of trust in governmental efforts (78,82,83). These findings display that perceived governmental efforts directly impact willingness to vaccinate (84,85). This finding reflects upon the pandemic's political ramifications (84,86,87) that have been introduced and its negative impact on citizens' willingness to vaccinate.…”
Section: Resultsmentioning
confidence: 84%
“…These findings display that perceived governmental efforts directly impact willingness to vaccinate (84,85). This finding reflects upon the pandemic's political ramifications (84,86,87) that have been introduced and its negative impact on citizens' willingness to vaccinate.…”
Section: Resultsmentioning
confidence: 84%
“…Some specific aspects of the COVID-19 pandemic seem to have exacerbated feelings of fear among the population, such as uncertainty about its spreading and evolution and the initial absence of vaccines (Ornell et al, 2020 ). While moderate levels of fear of COVID-19 may be helpful as they lead people to engage in protective behaviors, extreme levels of fear of COVID-19 may become detrimental to psychological health, as people may not think rationally when reacting to COVID-19 (Bochicchio et al, 2021 ; Garfin et al, 2020 ; Scandurra et al, 2021 ; Sloan et al, 2021 ). Previous studies demonstrated that the fear of COVID-19 is a significant predictor of depression, anxiety, and stress (Rodríguez-Hidalgo et al, 2020 ; Yıldırım et al, 2020 ) and it is plausible to hypothesize that this may be true even in pwMS, who perceive themselves as most at risk (Borriello & Ianniello, 2020 ; Foerch et al, 2020 ; Herman et al, 2020 ; Salari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, little research has been conducted to identify psychological correlates of vigilance in the prolonged COVID-19 pandemic situation. Most extant research on pandemic response focused on the early phases of the pandemic (e.g., [13][14][15][16]), and evidence has only begun to emerge with respect to how psychological factors such as future anxiety and pandemic-related fatigue are associated with compliance with pandemic measures (e.g., [16]). It may be expected that future anxiety due to COVID-19 can increase people's motivation to engage in behaviors for preventing the spread of the virus [17].…”
Section: Introductionmentioning
confidence: 99%
“…It may be expected that future anxiety due to COVID-19 can increase people's motivation to engage in behaviors for preventing the spread of the virus [17]. However, extant literature suggests that future anxiety may induce pandemic-related fatigue, which may, in turn, reduce engagement in protective behaviors [16], and research has yet to examine how future anxiety and pandemic-related fatigue relate to vigilance while the pandemic evolves through multiple waves. It is also important to identify segments of individuals who may be more/less likely to remain vigilant even when the pandemic situation seems to improve but is not completely under control.…”
Section: Introductionmentioning
confidence: 99%